The wolf wants in : a novel - McHugh, Laura (Spiegel & Grau, an imprint of Random House, a division of Penguin Random House LLC, 2019)
"Still reeling from her older brother's death, Sadie is looking for answers. It isn't unusual for someone to die young in Cutler county--there have been so many overdoses in recent years that an article in the Kansas City Star bemoaned the decimation of the next generation of farmers. But Sadie's brother wasn't an addict. And though his wife who found him said it was a heart attack, he was only thirty-six years old and has never had any health problems. Was it possible her brother didn't die from natural causes? Another tragedy has also recently struck the small Kansas county--Roger Calhoun and his young daughter Macey have been missing for months. In a town where everyone knows each other's business, the bitterness of the Calhoun's divorce and ensuing custody battle was public knowledge, and when the young girl's skull is identified in the woods, along with the bones of her father nearby, her mother, a notorious addict and an old friend of Sadie's, becomes a prime suspect. Meanwhile, Henley, a recent high-school graduate, is desperate to leave town and escape the shadow of her family's trouble-maker reputation and harsh poverty. Henley dreams of a bigger world and a better life outside of Kansas. As she plots her departure, she begins dating the son of the wealthiest man in town. Henley is drawn to the idea of a rich, easy life, but the boy starts to get aggressive and suffocating--showing up at her home with hardly a moment's notice, not letting her spend any time alone, and stalking her every move" --